Rola kobiet w hiszpańskich wyprawach zdobywczych w Ameryce Środkowej i Południowej w XVI w. - Grzegorzewska, Kinga (Acta Universitatis Lodziensis. Folia Historica, 2015)
I would like to present in this article the question of the participation of women in the martial and exploratory expeditions to Central and South America organized by the Spanish in the sixteenth century. Usually, descriptions of the expeditions are limited to the male participants, which is why in this article I would like to direct attention to the participation and activity of women in such enterprises. Native women performed serving functions of cooks, laundresses, porters, or aided the Spanish as interpreters and provided them with information. Sometimes they took part in expeditions in order to accompany their husbands or paramours, as female Indians were often gifted to the conquerors as slaves. Spanish women often joined expeditions of which one of the aims was to settle newly conquered territories. They would set off together with their husbands or paramours, often enjoying privileges which aggravated the other participants. Women took a variety of tasks upon themselves, frequently advising leaders in problematic situations. The article presents various forms of activity of the members of the fair sex during the expeditions, and their status and influence on the success of the undertakings.